ENTREPRENEURSHIP IN ROMANIA. COUNTRY REPORT 2013 - SZABÓ, Tünde-Petra; PETE, Ștefan; GYÖRFY , Lehel‐Zoltán; DÉZSI-BENYOVSZKI, Annamária; NAGY, Agnes (Presa Universitară Clujeană, 2017)
The Global Entrepreneurship Monitor (GEM) is the most important and comprehensive international study of entrepreneurship and the entrepreneurial environment. The GEM study in 2013 covers 75% of the world’s population and 90% of the world’s GDP. In Romania the study is conducted by the Babeş-Bolyai University of Cluj-Napoca, Faculty of Economics and Business Administration. A total of 2,021 adults were interviewed in the Adult Population Survey (APS) for this study in 2013. In order to assess the national conditions influencing entrepreneurial activity 36 national experts completed a closed questionnaire on factors related to entrepreneurial environment. The early-stage entrepreneurial activity rate in Romania in 2013 is 10.1% of the adult working age population. This rate is slightly higher than it was in 2012 (9.22%), it is higher than the rate registered in Croatia, Hungary and Slovakia and it is similar to the Central- Eastern European efficiency-driven economies’ (CEE) average measured in 2013. The share of nascent entrepreneurs decreased from 7.94% in 2012 to 6.2% in 2013. This rate is similar to Croatia, Hungary, Slovenia, and to the CEE average, but it is lower than the average of the world’s efficiency-driven economies. The share of young business entrepreneurs increased to 4.2% in 2013, from 3.81% in 2012.